Penggunaan Kontrasepsi KB Suntik 3 Bulan dan Hubunganya dengan Kenaikan Berat Badan dan Kejadian Hipertensi - Fadillah, Mutiara Nur (MPI Press, 2024)
Introduction: Contraception is an attempt to delay pregnancy, this effort can also be temporary or permanent. Weight gain is often caused by excessive food intake, lack of physical activity, genetics, drugs and use of birth control/hormonal injections. Hypertension is also a manifestation of disturbances in the hemodynamic balance of the cardiovascular system. Objective: To determine the relationship between the use of 3-month injectable birth control contraception with weight gain and the incidence of hypertension at the Curug Village Health Center in Curug Village in 2022. Method: This research uses a quantitative type of research, the research design used is cross-sectional. The population in this study was 568 3-month injectable contraceptive acceptors. The sample was taken using purposive sampling with the criteria of mothers using 3-month KB injectable contraception totaling 95 respondents. The research instruments used medical records and observation sheets, scales and sphygmomanometeir. This research uses chi-square test data analysis. Results: Based on the results of the chi-square test, weight gain with 3-month contraceptive injections showed a p-value of 0.037 (p<0.05). The incidence of hypertension with injectable contraceptives was found to have a p-value of 0.008 (p<0.05). Conclusion: There is a relationship between the use of injectable birth control contraception and body weight. There is a relationship between the incidence of hypertension and the use of 3-month injectable birth control contraception. The use of 3-month injectable birth control contraception can affect weight gain and the incidence of hypertension, especially in birth control acceptors who use it for more than one year.